2021
DOI: 10.1177/23259671211046625
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Repair, Augmentation, and Reconstruction of Knee Extensor Mechanism Disruption: A Retrospective Review

Abstract: Background: The loss of extensor mechanism continuity that occurs with patellar and quadriceps tendon rupture has devastating consequences on patient function. Purpose: To describe a treatment strategy for extensor mechanism disruption and evaluate the outcomes of 3 techniques: primary repair, repair with semitendinosus tendon autograft augmentation, and reconstruction with Achilles tendon allograft. Study Design: Case series; Level of evidence, 4. Methods: The authors reviewed surgeries for extensor mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…These findings are in accordance with previously reported data presenting the Achilles tendon allograft as an effective treatment for reconstructing ruptured patellar tendon [ 8 , 10 , 25 ]. Barrack et al [ 4 ] reported a summary average of clinical and functional Knee Society Score, which improved from 32 to 128 points, representing a highly significant improvement.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in accordance with previously reported data presenting the Achilles tendon allograft as an effective treatment for reconstructing ruptured patellar tendon [ 8 , 10 , 25 ]. Barrack et al [ 4 ] reported a summary average of clinical and functional Knee Society Score, which improved from 32 to 128 points, representing a highly significant improvement.…”
Section: Discussionsupporting
confidence: 94%
“…Primary repair is indicated for acute complete patellar tendon ruptures with good tissue quality ( 13 ). Transosseous tunnels or suture anchors are the most common methods of fixation.…”
Section: Patellar Tendon Rupturesmentioning
confidence: 99%
“…Tendon allografts have an important role in tendon reconstruction in a number of anatomical sites, being able to overcome the obstacles of poor tissue quality and availability of autologous tissue besides avoiding the donor site morbidity associated with autologous grafts [ 27 , 28 ]. They have become increasingly popular for a variety of tendon repairs, especially when there is a deficient, scarred, and retracted tendon, preventing a primary repair [29] , [30] , [31] . Besides, allografts provide a sufficiently long tendon length that allows various methods of fixation and suture [32] .…”
Section: Discussionmentioning
confidence: 99%